Optimal monitoring of credit-based emissions trading under asymmetric information - Ian A. MacKenzie; Markus Ohndorf (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
Project-based emissions trading schemes, like the Clean Development Mechanism, are particularly prone to problems of asymmetric information between project parties and the regulator. In this paper, we extend the general framework on incomplete enforcement of policy instruments to reflect the particularities of credit-based mechanisms. The main focus of the analysis is to determine the regulator's optimal spot-check frequency given plausible assumptions of incomplete enforcement under asymmetric information on reduction costs and heterogeneous verifiability of projects. We find that, depending on the actual abatement cost and penalty schemes, optimal monitoring for credit-based systems is often discontinuous and significantly differs from the one to be applied for cap-and-trade schemes or environmental taxes. We conclude that, in a real-world context, project admission should ultimately be based on the criterion of verifiability.
Keywords: K32; D42; D82; Q58; 330; Environmental regulation; Project-based emissions trading systems; Audits and compliance; Umweltstandard; Rechtsdurchsetzung; Emissionshandel; Asymmetrische Information; Monopol; Theorie